2021
DOI: 10.1155/2021/6672656
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Analysis of Green Technology Innovation from Green Patents in China

Abstract: Green technology innovation is essential to promoting not only the construction of ecological civilization but also the fundamental means of achieving sustainable development. Taking research and development (R&D) investment, CO2 emissions, and other related factors into account, this study constructed an extended logarithmic mean Divisia index (LMDI) decomposition model for the change in the number of green technology patent applications to quantify the contribution of each driving factor based on green p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Some scholars suggested that to distinguish between inter-organizational and intra-organizational relationships caused by non-green innovation, green patents should be regarded as an indicator of green innovation [ 53 ]. Therefore, in this study, we drew on the studies of some other scholars [ 54 , 55 ] and used the natural logarithm of the number of environmental green patent applications to measure the level of green innovation across countries.…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars suggested that to distinguish between inter-organizational and intra-organizational relationships caused by non-green innovation, green patents should be regarded as an indicator of green innovation [ 53 ]. Therefore, in this study, we drew on the studies of some other scholars [ 54 , 55 ] and used the natural logarithm of the number of environmental green patent applications to measure the level of green innovation across countries.…”
Section: Methodsmentioning
confidence: 99%
“…Global studies Studies that did not mention names of countries' studies (Mehta et al, 2019;Prajapati et al, 2021;) (Ahmad, 2021;Avotra et al, 2021;Cai et al, 2019;Cao et al, 2021;Cao and Niu, 2022;Chang et al, 2021;Chen and Chen, 2021;Chen et al, 2019;Dong et al, 2020;Feng et al, 2021;Geng et al, 2022;Huang and Chen, 2022;Jin, 2021;Kung et al, 2022;Lee et al, 2022;Li and Zhao, 2021;Li et al, 2020;Li et al, 2022;Ma et al, 2021;Pan et al, 2021;Qu et al, 2022;Ren et al, 2020;Shao and Xue, 2022;Tu et al, 2021;G. Wang et al, 2022;L.…”
Section: Studies Conducted In Panel Of Countries Along With Indiamentioning
confidence: 99%
“…On the other hand, green financing also promotes green technology innovations (energy, transport, construction, wastewater treatment, chemical processing, and material innovation), which are significant tech developments and breakthroughs advancing efforts to decarbonization and elevating green growth (Badri Shah, 2021;Chen and Chen, 2021;Debrah et al, 2022;Jin, 2021;Li et al, 2020;Ma et al, 2021;Zhou et al, 2020;. Followed the studies by (Al Mamun et al, 2022;Chang et al, 2021;Lin et al, 2023;Nawaz et al, 2021;Zhang et al, 2022) reveal that green financing efforts are critical in minimizing the impacts of climate change and fostering sustainable growth.…”
Section: Introduction 1background and Context Of The Studymentioning
confidence: 99%
See 1 more Smart Citation